China’s Efforts to Protect the Seas - Gong, Lina (2017)
The convening of the first Ocean Conference by the United Nations earlier this month illustrates the pressing need to curb and reverse marine environmental degradation. This issue is critical for China given its growing challenges from marine environmental degradation. China needs to develop its marine economy sustainably and enhance law enforcement and international cooperation.